Occurrence of parasites in domestic ducks from rural areas of Narayanganj (Bangladesh Journal of Zoology, 2019)
Thirty six domestic ducks (Anas platyrhynchos) were examined to observe the occurrence of ecto and endoparasites. Altogether seven species of ectoparasites namely Anaticola crassicornis, Lipeurus caponis, Goniocotes hologaster, Menopon gallinae, Menacanthus stramineus, Holomenopon leucpxanthum and Dermanyssus gallinae were observed and identified. L. caponis showed the highest prevalence both in male and female (100%). Mean intensity of A. crassicornis in female ducks was the highest (14.5 ± 2.36) followed by L. caponis (12.5 ± 3.21). The lowest mean intensity was of G. hologaster (2.5 ± 1.41) in male ducks. Prevalence of D. gallinae was higher in male (62.5%) than in female (40%). The maximum percentage of ectoparasites was recovered from wing feather (38.62) followed by trunk (23.85) and skin (23.44). Among the endoparasites, the occurrence of cestodes (77.78%) was the highest with the topmost intensity (51.43 ± 4.88). The highest prevalence was of Hymenolepis columbae and Hymenolepis diminuta (60%). Echinoparyphium recurvatum, Echinostoma revolutum and Tracheohilus sisowi showed the similar prevalence (30%) in male ducks. Patagifer bilobus showed the peak mean intensity in both the male and female ducks. Only one species of nematode, Ascaridia galli was recovered. The maximum endohelminths were found in the small intestine (48.30%) followed by duodenum (31.36%) and rectum (15.32%).Bangladesh J. Zool. 47(2): 315-323, 2019